Morphine and morphine glucuronides in serum of heroin consumers and in heroin-related deaths determined by HPLC with native fluorescence detection - Aderjan, Rolf; Hofmann, Sybille; Schmitt, Georg; Skopp, Gisela (Journal of analytical toxicology, 1995)
A simple, rapid, and sensitive high-performance liquid chromatographic method for the simultaneous determination of serum morphine, morphine-6-glucuronide (M6G), and morphine-3-glucuronide (M3G) based on native fluorescence detection is described. For the extraction of drugs and their metabolites, 200 µL serum was applied to 50 mg of a commercially available octylsilan phase. After isocratic separation in two steps (6.5 min) by reversed phase, the compounds were determined at an excitation wavelength of 245 nm and an emission wavelength of 345 nm (the limit of detection was approximately 5 µg/L for each compound). The concentrations of morphine, M6G (with respect to its potential analgesic activity), and M3G were investigated in 20 heroin addicts in police custody and in 10 heroin-associated deaths. The ratios between M6G or M3G and the morphine concentrations and between M6G and M3G are related to the morphine concentration and consequently depend on the time elapsed since the last administration of morphine or heroin. Consequently, the M6G values were found to be higher in cases of death than in the living addicts. By considering the M6G/morphine or M3G/morphine ratios, the narcotic effect of heroin as reflected by morphine and its metabolite concentrations in impaired addicts and cases of fatal poisoning can be better assessed than by use of the morphine concentration alone.